Apprentices’ Resources at Work and School in Switzerland: A Person-Centred Approach - Lüthi, Fabienne; Stalder, Barbara E.; Elfering, Achim (International Journal for Research in Vocational Education and Training, 2021)
Context: Providing learners with quality resources at work and school is a key element of apprenticeships and is essential for developing vocational competencies and successful vocational careers. Drawing on previous research on situational and personal resources, we first explored work-related and school-related resource profiles of apprentices’ learning environments. We further analysed how core self-evaluations are linked to resource profiles and examined whether learners’ apprenticeship satisfaction and occupational commitment varied according to the resource profiles. Approach: We used latent profile analysis and multinomial logistic regressions, applying an integrative, person-centred approach. Our data came from the Swiss longitudinal study "Transition from Education to Employment" (TREE). The sample consisted of 1,185 apprentices enrolled in the second year of their apprenticeship. Findings: We found four profiles of situational resources (e.g., instruction quality, climate, learning opportunities, autonomy, and demands) at the two learning locations. The profiles embodied different patterns and levels of situational resources. Two profiles were characterised by overall high or average levels of situational resources at both learning locations; the other two illustrated a stark contrast between the resources provided in the workplace and at school. Learners with higher core self-evaluations were more likely to be in profiles with higher situational resources. Apprentices in more beneficial profiles were more satisfied with their apprenticeships and more committed to their occupations than those in profiles with lower resources. Conclusion: The results confirm the importance of providing apprentices with challenging, empowering, and supportive learning environments in the workplace and at vocational schools. To support learning and positive career development in apprenticeships, educators should strengthen learners’ core self-evaluations to empower them to shape their learning according to their needs.